Practical aspects of declarative languages : 19th International Symposium, PADL 2017, Paris, France, January 16-17, 2017, Proceedings /: 19th International Symposium, PADL 2017, Paris, France, January 16-17, 2017, Proceedings. (2017) - Unknown
No abstract available